Digital audio theory : a practical guide - Bennett, Christopher L. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Digital Audio Theory: A Practical Guide bridges the fundamental concepts and equations of digital audio with their real-world implementation in an accessible introduction, with dozens of programming examples and projects. Starting with digital audio conversion, then segueing into filtering and finally real-time spectral processing, Digital Audio Theory introduces the uninitiated reader to signal processing principles and techniques used in audio effects and virtual instruments that are found in digital audio workstations. Every chapter includes programming snippets for the reader to hear, explore, and experiment with digital audio concepts. Practical projects challenge the reader, providing hands-on experience in designing real-time audio effects, building FIR and IIR filters, applying noise reduction and feedback control, measuring impulse responses, software synthesis, and much more. Music technologists, recording engineers, and students of these fields will welcome Bennett's approach, which targets readers with a background in music, sound, and recording. This guide is suitable for all levels of knowledge in mathematics, signals and systems, and linear circuits. Code for the programming examples and accompanying videos made by the author can be found on the companion website, DigitalAudioTheory.com"--
1 Introduction1.1 Describing audio signals1.2 Digital audio basics1.3 Describing audio systems1.4 Further reading1.5 Challenges1.6 Project- audio playback2 Complex vectors and phasors2.1 Complex number representation and operations2.2 Complex conjugates2.3 Phasors2.4 Beat frequencies2.5 Challenges2.6 Project- AM and FM synthesisBibliography3 Sampling3.1 Phasor representation on the complex plane3.2 Nyquist frequency3.3 Time shift operators3.4 Sampling a continuous signal3.5 Jitter3.6 ChallengesBibliography4 Aliasing and reconstruction4.1 Under-sampling4.2 Predicting the alias frequency4.3 Anti-aliasing filter4.4 Reconstruction4.5 Challenges4.6 Project- aliasingBibliography5 Quantization5.1 Quantization resolution5.2 Audio buffers5.3 Sample-and-hold circuit5.4 Quantization error (eq)5.5 Pulse code modulation5.6 ChallengesBibliography6 Dither6.1 Signal-to-Error Ratio (SER)6.2 SER at low signal levels6.3 Applying dither6.4 Triangular PDF dither6.5 High-frequency dither6.6 Challenges6.7 Project- dither effectsBibliography7 DSP basics7.1 Time-shift operators7.2 Time-reversal operator7.3 Time scaling7.4 Block diagrams7.5 Difference equations7.6 Canonical form7.7 Challenges7.8 Project- plucked string modelBibliography8 FIR filters8.1 FIR filters by way of example8.2 Impulse response8.3 Convolution8.4 Cross-correlation8.5 FIR filter phase8.6 Designing FIR filters8.7 Challenges8.8 Project- FIR filtersBibliography9 z-Domain9.1 Frequency response9.2 Magnitude response9.3 Comb filters9.4 z-Transform9.5 Pole/zero plots9.6 Filter phase response9.7 Group delay9.8 Challenges10 IIR filters10.1 General characteristics of IIR filters10.2 IIR filter transfer functions10.3 IIR filter stability10.4 Second-order resonators10.5 Biquadratic filters10.6 Proportional parametric EQ10.7 Forward-reverse filtering10.8 Challenges10.9 Project- resonatorBibliography11 Impulse response measurements11.1 Noise reduction through averaging11.2 Capturing IRs with MLS11.3 Capturing IRs with ESS11.4 Challenges11.5 Project- room response measurementsBibliography12 Discrete Fourier transform12.1 Discretizing a transfer function12.2 Sampling the frequency response12.3 The DFT and inverse discrete Fourier transform12.4 Twiddle factor12.5 Properties of the DFT12.6 Revisiting sampling in the frequency domain12.7 Frequency interpolation12.8 Challenges12.9 Project- spectral filtering13 Real-time spectral processing13.1 Filtering in the frequency domain13.2 Windowing13.3 Constant overlap and add13.4 Spectrograms13.5 Challenges13.6 Project- automatic feedback control14 Analog modeling14.1 Derivation of the z-transform14.2 Impulse invariance14.3 Bilinear transformation14.4 Frequency sampling14.5 Non-linear modeling with ESS14.6 ChallengesBibliography
"A Focal Press Book" -- taken from front cover.
OCLC-licensed vendor bibliographic record.
Keywords: Sound -- Recording and reproducing -- Digital techniques; Signal processing -- Digital techniques; Digital communications; SCIENCE / Acoustics & Sound; TECHNOLOGY / Electronics / Digital